Innovative vaccine approaches-a Keystone Symposia report - Cable, J; Rappuoli, R; Klemm, EJ; Kang, G; Mutreja, A; Wright, GJ; Pizza, M; Castro, SA; Hoffmann, JP; Alter, G; Carfi, A; Pollard, AJ; et al. (Wiley, 2022)
The rapid development of COVID-19 vaccines was the result of decades of research to establish flexible vaccine platforms and understand pathogens with pandemic potential, as well as several novel changes to the vaccine discovery and development processes that partnered industry and governments. And while vaccines offer the potential to drastically improve global health, low-and-middle-income countries around the world often experience reduced access to vaccines and reduced vaccine efficacy. Addressing these issues will require novel vaccine approaches and platforms, deeper insight how vaccines mediate protection, and innovative trial designs and models. On June 28-30, 2021, experts in vaccine research, development, manufacturing, and deployment met virtually for the Keystone eSymposium "Innovative Vaccine Approaches" to discuss advances in vaccine research and development.